Performance Comparison of Tauri and Electron Frameworks in Multiplatform Desktop Application Development - Prayogo Kosasih W; Mychael Engel (bit-Tech, 2026)
In the modern startup ecosystem, the ability to rapidly extend web-based products into desktop platforms while maintaining high performance and resource efficiency has become increasingly important. Electron has long been a dominant framework for building cross-platform desktop applications using web technologies, primarily due to its mature ecosystem and development convenience. However, Electron-based applications are often criticized for large distribution sizes and high runtime resource consumption because they bundle a full Chromium browser engine and Node.js runtime. As an alternative, Tauri has emerged as a lightweight framework that leverages Rust for backend functionality and utilizes the operating system’s native WebView for rendering the user interface. This study aims to empirically compare the performance of Electron and Tauri in multiplatform desktop application development using the same web-based codebase. A quantitative experimental benchmarking approach was employed by developing two identical prototype applications derived from a Next.js web application and packaging them separately using Electron and Tauri. Performance was evaluated using four key metrics installer file size, RAM usage, CPU utilization, and build time. Experimental results show that Tauri significantly outperforms Electron in resource efficiency. The Tauri application produced an installer size approximately 99% smaller than Electron and demonstrated up to ten times lower RAM usage during idle operation. CPU usage was also slightly lower in Tauri during both idle and active conditions. However, Tauri exhibited longer build times due to Rust’s compilation process. These findings provide practical insights for technology decision-makers and developers in selecting an efficient framework for scalable desktop application development.